Costa Rican teachers’ conceptions on Science investigation within the scope of a complexity model - Retana Alvarado, Diego Armando (2016)
This research, following an exploratory and descriptive approach, aims to analyse the conceptions on school investigation in the Implementation of the Education Programme on Scientific Thinking. It is based on an inquiry process from The Ministry of Public Education of Costa Rica, in the 1st and 2nd Primary Education Cycles, conducted by a group of science teachers, during the 2015 school year. During the methodological stage, a mixed methods approach and an exploratory sequential design (DEXPLOS) were used. On the one hand, four Science advisers elaborated narratives that were analysed through an emerging narrative design; on the other hand, questionnaires were given to twelve teachers focusing on investigation, pedagogical-content knowledge and teachers’ training needs. Results suggest the presence of empiricist conceptions nuanced with positivist ones, defining a researcher and a traditional teaching model, respectively, with a progressive tendency towards higher levels of evolutionary complexity. These conceptions determine in-class actions and favourably influence the design, planning and implementation of research processes in Primary Education. The transition from an intermediate level to a reference one can be facilitated by initial and continuous teacher training.